Factors contributing to poor glycaemic control in diabetic patients at Mopani District - N.H. Shiluban (AOSIS, 2009)
Diabetes mellitus is not only a major burden in the developed world, it is also an increasing health problem in less developed countries. Although health education could be a tool to achieve better glycaemic control, it is important to understand that health education should be adjusted to patients' literacy, cultural environment and economic status. Among other factors, lack of money has an influence on the outcome of diabetes mellitus. Thus the purpose of the study is to identify factors contributing to poor glycaemia control in diabetic patients. Data was collected using self-report questionnaire on a convenient sample of 32 diabetic patients and unstructured, open-ended interviews on eight patients' inorder to allow them freedom of expressing themselves with regard to factors that contribute to poor glycaemic control on diabetic patients. Data was then analysed using a computer program called Statistical Package for Social Sciences. The socioeconomic factors appeared to have significant influence on glycaemic control among participants, for instance 75% of the total subjects (32) indicated that they experienced problems of accessing health care services due to lack of money. Ignorance related to where to seek support system such as educational programme, and nutrition counselling were factors that were identified to contribute to diabetic patients' poor glycaemia control. Permission to conduct the study was obtained from the Provincial Department of Health and the managers of the institutions where the study was conducted. Recommendations for dealing with the identified factors have been formulated.